Study on food-feed competitive efficiency of Moringa fodder in the active Brahmaputra-Jamuna Floodplain Agro-Ecological Zone of Bangladesh (Bangladesh Journal of Animal Science, 2019)
The research work was carried out to evaluate the food-feed competitive efficiency of Moringa fodder in the Active Brahmaputra-Jamuna Floodplain Agro-Ecological Zone (ABJF-AEZ) of Bangladesh. For determining the competitive land use efficiency of Mornga feed (Mf) production, the Moringa fodder was cultivated in Gaibandha district at ABJF-AEZ with four replications. The annual dry matter (DM) yield of Moringa at on-farm condition was the height (26.67 ton/ha) and it was varied significantly (P